Information-Motivation-Behavioural Skills Model-based intervention effectively improved hygiene-related self-efficacy and practice among the primary caregivers of the under-three indigenous children in Malaysia - Minhat, Halimatus Sakdiah; Zakaria, Liyanatul Najwa (John Wiley and Sons, 2022)
Poor hygiene practice has been an ongoing issue among the Orang Asli community in Malaysia and is strongly linked to poor child growth and malnutrition. A theory-based intervention was developed and implemented to improve the knowledge, attitude, self-efficacy and practice related to hygiene among the primary caregivers of the under-three Orang Asli children. A single blinded clustered randomized control trial was conducted involving random allocation of five government health clinics into intervention and control groups, using random block method. Using the Information-Motivation-Behaviour Skills (IMB) model, an intervention was developed and delivered in the form of health talks, video presentation, group counselling and guided practical sessions. Knowledge (information) and attitude (motivation) on hygiene, self-efficacy (behavioural skills) towards practising good hygiene and hygiene practice were measured at baseline, 1 and 3 months follow-up. A total of 166 participants were recruited for the study. The overall between groups comparison showed significant different between mean scores for self-efficacy (MD = 1.22 [0.36, 2.10]) and hygiene practice (MD = 1.70 [0.47, 2.93]), with moderate effect size of 0.3 and 0.36 respectively. Self-efficacy and hygiene practice had significant different in mean scores at 2 time points (at 1- and 3-month post-intervention) with the highest effect size is observed for practice at 1- month post-intervention (ES = 0.74). Within the intervention group, significant improvement of knowledge (MD = 1.06 [0.49–1.63]), attitude (MD = 1.04 [−0.56, 2.65]) and hygiene practice (MD = 1.78 [0.04, 3.52]) mean scores were observed at 3-month post-intervention as compared to the baseline measurement. IMB-based intervention was found to effectively improved self-efficacy and practice related to hygiene among the primary caregivers of the Orang Asli children. However, the moderate effect size may reflect the needs to revise the intervention in order to increase its impact and transferability.